FX trading... LIVE!: Dealer behaviour and trading systems in foreign exchange markets - Geir Høidal Bjønnes; Dagfinn Rime (University of Oslo, Department of Economics, 2000)
The introduction of electronic broker systems in the foreign exchange (FX) market at the end of 1992 changed the structure of the market and opened new channels for trading. We study the impact of these systems on dealer behavior, using a unique data set on the complete transactions of four FX dealers. We find some support for an information effect in incoming trades conducted directly (bilaterally). For trades executed by electronic broker systems we find no information effects, but we find that sequences of trades in cumulative flow may be informative for prices. The new electronic systems have changed how dealers control their inventories by introducing new channels for this purpose. We find that dealers now control inventory by outgoing trades on electronic brokers, while outgoing trades earlier was regarded as unattractive for inventory control. Comparing our results to previous research indicates that the introduction of electronic brokers have changed the behavior of dealers.
Keywords: F31; G15; 330; Foreign Exchange; Microstructure; Trading; Devisenhandel; Börsenmakler; Mikrostrukturanalyse; Norwegen